Pengaruh Bauran Pemasaran Terhadap Keputusan Pembelian Konsumen Produk Kartu Perdana Pascabayar Halo Pada PT. Telkomsel Grapari Makassar - Safrida Safrida; Musmulyadi Musmulyadi (COSTING : Journal of Economic, Business and Accounting, 2021)
This research was conducted with the aim of: (1) examining and analyzing the effect of the product on consumer purchasing decisions for postpaid hello card products; (2) examining and analyzing the effect of price on consumer purchasing decisions for postpaid starter pack hello; (3) examining and analyzing the effect of promotion on consumer purchasing decisions for postpaid starter pack hello; (4) examining and analyzing the effect of place on consumer purchasing decisions for postpaid starter pack hello; (5) examining and analyzing the four factors that have the most dominant influence on consumer purchasing decisions for postpaid hello card products. This study uses primary data and secondary data. In this study, the sample used was 100 consumers. based on secondary data at the end of 2015 to December 2016. Data was collected through questionnaires and data tabulation was carried out. Methods of data analysis using multiple linear regression analysis and analysis of the coefficient of determination and descriptive analysis with the help of the Statistical Product and Service Solutions (SPSS) program. These results indicate that: (1) the product variable has a positive but insignificant effect on consumer decision making to buy postpaid starter pack hello: (2) the price variable has a positive and significant effect on the decision to buy a postpaid starter pack hello: (3) promotion variable has a significant effect on the decision to buy postpaid starter pack hello: (4) the place variable does not have a positive and significant effect on the decision to buy the postpaid starter card hello: (5) the most dominant variable influencing decision making is the price variable. Keywords: Product, Price, Place, Promotion, and Purchase Decision